Kontribusi Imam al-RÃ¢fiâÃ® dan Imam al-NawawÃ® dalam Penataan Keragaman Pendapat Hukum Mazhab ShÃ¢fiâÃ® - Saleh, Abdul MunÃ¢Â€Â™im (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
The diversity of legal opinions in the ShÃ¢fiâÃ® school of thought (madhhab), in the form of old opinion (qawl qadîm) and new opinion (qawl jadîd) and the ijtihâd activities that pertained Â to some centuries after the passing away of al-ShÃ¢fiâÃ®, has brought this madhhab into encounter with serious problems in selecting the law. In such a situation, al-RÃ¢fiâÃ® and al-Nawawî came into the fore as muharrir (selector) to cope with this uncertainty. This research tries to analyze all scientific activities of the two scholars using the theory of tarjîh. This research found out that they attempted to establish a legal certainty in the ShÃ¢fiâÃ® school of law through the making of new mixed system of tarjîh to ensure which opinions deserve to be regarded as valid from the viewpoint of ShÃ¢fiâÃ® madhhab. This achievement contributes to the enrichment of ShÃ¢fiâÃ® madhhab as a legal school consisting of a great variety of legal opinions that equips itself with procedures of selection used as norms of everyday life.